If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(5x + -6) = 152 Reorder the terms: 8(-6 + 5x) = 152 (-6 * 8 + 5x * 8) = 152 (-48 + 40x) = 152 Solving -48 + 40x = 152 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + 40x = 152 + 48 Combine like terms: -48 + 48 = 0 0 + 40x = 152 + 48 40x = 152 + 48 Combine like terms: 152 + 48 = 200 40x = 200 Divide each side by '40'. x = 5 Simplifying x = 5
| 2x=8+y | | -18+12x=10x+14 | | -8=-(4)+4 | | =x^4-4x^3+3x^2-4x+2 | | 11.95x+4.95=64.70 | | 7=m/2 | | 11-8x=75-36x | | 8p^2-2p+15=0 | | -2x+y=-8 | | 4n-1=-29 | | 0.5y=-6 | | 7-3(p+5)=27 | | 56x^3/(42x^2) | | 3(6-b)-33=27b-5(3+6b) | | 58+11x=6x+92 | | Mx+mx=p | | 3(4x+3)-8=13 | | -0.4x+20=-16 | | a=-10+2b | | 3x-4=4(x+3) | | 3.5x+8=x | | m-6m=8 | | 3.5x=8 | | 7u-w=u-6w | | -2/22x7/41 | | 16/10+9/2-21/4 | | 48x^2+22x-25=0 | | -305=5(8n-5) | | (5-3x)-2(-4x+6)= | | 15-x+6y-2= | | 3x-100=6x+26 | | -x^4+7x^2-6=0 |